2013
DOI: 10.1097/tp.0b013e31827ac322
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Infected Kidney Graft Recipients Managed With an Early Corticosteroid Withdrawal Protocol

Abstract: Background The outcome of HIV-infected kidney transplant recipients managed with an early corticosteroid withdrawal protocol is not known. Methods Eleven consecutive HIV-infected patients with undetectable plasma HIV RNA and >200/mm3 CD4+ T-cells underwent deceased (n=8) or living donor (n=3) kidney transplantation at our center. All were managed with an early corticosteroid withdrawal protocol; 9 of 11 received anti-thymocyte globulin and 2 received basiliximab induction. We analyzed patient and graft outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 36 publications
3
16
0
Order By: Relevance
“…The same pattern of immunosuppressive treatment has been observed in other studies. In all recent studies, CNIs were largely utilized, and interestingly, some reports have suggested that adequate immunosuppression, without maintenance steroids, may be possible in HIV-infected recipients (11,(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…The same pattern of immunosuppressive treatment has been observed in other studies. In all recent studies, CNIs were largely utilized, and interestingly, some reports have suggested that adequate immunosuppression, without maintenance steroids, may be possible in HIV-infected recipients (11,(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to most of the above studies in which steroids were incorporated into the treatment regimen, Muthukumar et al [15] have recently reported the use of a 'steroid-free' approach in 11 HIVþ recipients under induction with rabbit antithymocyte globulin followed by tacrolimus-mycophenolate mofetil maintenance therapy. One-year patient survival was 100% and by 3 years it was 90%.…”
Section: Acute Rejectionmentioning
confidence: 99%
“…In agreement with a recent report by Muthukumar et al . , only one case of NODAT was observed in recipients on steroid‐free regimen. In addition, the only episode of acute myocardial infarction observed in our population occurred in a patient taking steroids.…”
Section: Discussionmentioning
confidence: 95%
“…Muthukumar et al . recently reported a very low rate of AR in HIV+ kidney graft recipients with early corticosteroid withdrawal who underwent induction therapy with thymoglobulin. The incidence of infections observed with this approach did not differ from that reported in HIV‐negative recipients treated with lymphocyte‐depleting antibodies .…”
Section: Discussionmentioning
confidence: 99%